IMPACT OF COMPENSATION AND MOTIVATION TO THE PURPOSE OF THE WORK IN THE PEOPLE OF P. GENKI KIRANA INTERNUSA MAKASSAR - Caezar Fachran; Abdi Akbar, Chalid Imran Musa, Uhud Darmawan Natsir, Rezky Amalia Hamka (CV. ADIBA AISHA AMIRA, 2024)
The results of this study show that compensation has a positive and significant impact on job satisfaction, motivation has positive and meaningful impact on employment satisfaction as well as compensation and motivation simultaneously have a significant and positive effect on employee satisfaction. This means that the better the compensation, the better and the more positive the employee's satisfaction will be. The relationship between compensation and motivation is complex and interrelated. Both play an important role in determining employee performance and job satisfaction. A balance between compensation and motivation is the key to maximizing job satisfaction.